35 Years of Development and Regulation of Private Security in Slovenia – Between Strengths, Opportunities and Risks - Andrej, Sotlar (Magyar Rendészet, 2025)
Modern private security has been developing in Slovenia for the past 35 years. During these years, it has been heavily regulated, as no other security organisation or activity has been subject to three laws in such a short period of time. Compared to EU countries, Slovenian private security is well regulated, as evidenced by some international studies. Our research findings reveal several strengths of private security regulation in Slovenia, but even more opportunities and risks that will need to be addressed in the future regulation of this field.